Evaluation of bio-diesel properties: a statistical approach. Issue 3 (3rd April 2017) - Murugesan, A.; Subramaniam, D.; Avinash, A.; Sasikumar, P.
ABSTRACT: In this work, methyl esters of Pungamia (MEOP), ethyl esters of Pungamia (EEOP), and ethyl esters of Neem (EEON) were primarily produced by means of transesterification process using sodium methoxide (mixture of sodium hydroxide and methanol) and potassium methoxide (mixture of potassium hydroxide and methanol). Further, the fuel properties such as calorific value, flash point, density and viscosity of methyl and ethyl esters were determined using ASTM specified equipment. Also, the association between different blend ratios and fuel type with fuel properties was gauged with an assistance of two-way analysis of variance. The experimental outcomes revealed that the maximum ester content of bio-diesel was witnessed for potassium hydroxide catalyst and the quantity of catalyst used was less than that with sodium hydroxide for the same mass of the feedstock oil. Overall, the statistical analysis disclosed that there is a significant difference in the fuel properties of the different combination of fuel type and blend ratios.